Magnetocaloric Effect in Uncoated Gd55Al20Co25 Amorphous Wires - Xing,Dawei (2015)
The Gd55Al20Co25 amorphous wires exhibit a relatively strong magnetocaloric effect (MCE). These melt-extracted amorphous wires display second-order magnetic transition (SOMT) and the value of maximal magnetic entropy (–ΔSm) for the melt-extracted wires is calculated to be ~9.7 J·kg–1·K–1 around the Curie point (TC) of ~110 K with applied field of 5 T. Moreover, the melt-extracted amorphous wires show a high refrigerating efficiency with a relatively large cooling power (RCP, ~804 J·kg–1) and refrigeration capacity (RC, ~580 J·kg–1) under an applied magnetic field of 5T due to the broad paramagnetic-ferromagnetic (PM-FM) region associated with amorphous alloys. These favorable properties make melt-extracted Gd-based amorphous wires to be the potential refrigerant for magnetic refrigeration (MR) of liquid oxygen.